Self-initiated photocatalytic polymerization of tough and flexible polyacrylamide hydrogel/polymeric semiconductor c3n4composites - Suphatchaya Lamkhao (2018)
© 2017, Tokai University. All rights reserved. Polyacrylamide (PAM)/g-C 3 N 4 composite materials were prepared by the self-initiation of C 3 N 4 via its photocatalytic activity. Radical species were produced during illumination of g-C 3 N 4 and can initiate the formation of the PAM/C 3 N 4 composite. The effect of charcoal composited to C 3 N 4 was also investigated. The physical properties of the PAM/g-C 3 N 4 and PAM/g-C 3 N 4 -charcoal composite materials were analyzed using SEM technique. Photocatalytic reduction of chromium (VI) to chromium (III) was validated using the composites.